Das diferentes relações contraídas pelos textos publicitários televisuais - Mattana, Luciano (2017)
The present thesis is interested in the television communication process, proposing to examine, in specific, the advertising discourse, with the main objective to analyze the relations contracted between advertising texts and the consumer market, considering the product promoted characteristics, its consumption logics and its target audience. In other words, we question the interference of these aspects, as well as the product aggregated values, in the discursive and expressive configuration of the television advertising texts, in the strategies choices to interpellate their potential consumers. For a better understanding of the publicity texts construction process under examination, the research is based on european semiotics principles and foundations, as conceived by Hjelmslev, Greimas, Barthes, trying to translate and articulate, from a methodological approach, theese theorists conceptions, so as to apply them in some analysis path to describe this specific discourse type: the television advertising, in its different configuration modalities. The research corpus was composed by twelve telvisuals commercials, that was broadcasted nationally during the RGT programming, through its affiliate RBSTV, between 14 and 27.07.2014. Even with many different narratives and configurations, some regularities have been identified: if the advertised products and their consumption logics are not the same and they even belong to different sectors, if they are intended for different consumer categories, if the narratives are diverse, if their protagonists are configured differently, if the scenarios vary, this research allowed to identify many common aspects, recurrences that do not depend on the target audience characteristics, the product advertised types and even the logics that govern their consumption, contradicting the initial assumption, that these factors would be definitive in the advertising set-up.